Meningkatkan Kualitas Hidup Masyarakat melalui Pembinaan Keagamaan: Program Pengabdian Komprehensif di Desa Lekopancing: Improving the Quality of Community Life through Religious Development: Comprehensive Community Service Program in Lekopancing Village - Sirajuddin, Sirajuddin; Muhammad, Muhammad (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The Student Community Service Program (KKN) is one of the Three Pillars of Higher Education (Tri Dharma Perguruan Tinggi) in the aspect of community service. This study aimed to evaluate the role of the 7th batch of STIBA Makassar KKN students in providing religious development programs for the community of Lekopancing Village, Maros Regency. Prior to implementation, a community needs analysis was conducted using the SOAR Analysis method. Based on the analysis results, a work program was formulated, encompassing Ramadan Short Course, Al-Qur'an Teaching, Night Vigil and Prayer, 20 Days of Ramadan Daurah, Tahsīn al-Qur'an (Qur'anic Recitation Improvement), Funeral Management Training, Pious Children Festival, Imam for Rawatib Prayers, Cupping and Ruqyah Shar'iyah (Prophetic Spiritual Healing), Friday Prayer Imam and Khotbah Jumat (Sermon), School Teaching Program, Breaking Fast Together and Tausiah (Religious Lecture), Dawn Kultum (Short Lecture), Social Service, and Tarawih Sermon. All programs were successfully implemented and demonstrated initial results in accordance with the objectives set for enhancing the religious development of the Lekopancing Village community.